Formation of human resources and scientific production in Science Education - Ediane Maria Gheno; Scheila Raquel Rempel; Luiz Felipe Sfoggia da Mata; Jessié Martins Gutierres; Regina Maria Guaragna; Rochele Loguercio; Luciana Calabró; Diogo Onofre Souza (Amazônia, 2021)
This article investigated whether the number of supervised students (masters and doctors/PhD) per professor impacts in the average number of periodic documents per student, and it evaluated the contributions to the production of scientific knowledge for the area of Science Education in the context of the Programa de Pós-Graduação em Educação em Ciências: Química da Vida e Saúde-PPGQVS (Universidade Federal do Rio Grande do Sul, Universidade Federal de Santa Maria, Universidade Federal do Rio Grande, and Universidade Federal do Pampa), from 2013 to 2019. The theoretical framework discusses the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) Evaluation System in the area of Teaching and Education in Science in Brazil. It is a descriptive study, with a qualitative and quantitative approach, which uses mixed analysis techniques: bibliometrics and scientometrics indicators and Content Analysis (Bardin). Data collection took place on the Sucupira Platform and on the periodical’s website. As a results, it was identified that the average number of documents per student is not affected by the number of students who have their professor. The most researched topics were “Science Teaching” (26.0%), “Teacher Training” (24.3%) and “Educational Policies” (15.7%). Based on the training of masters and doctors along with the production and dissemination of scientific knowledge, the contribution of the PPGQVS to the area of Science Education in the country becomes evident.